Ontstaan en groei van ’n seminarium aan die Fakulteit Teologie Stellenbosch en ander ontwikkelinge in die teologiese opleiding van die Ned Geref Kerk in die Sinode van Wes-Kaapland.: ’n Kritiese refleksie oor die deurbrake, kompleksiteite en uitdagings van teologiese opleiding - Marais, Jan Frederick (Stellenbosch theological journal, 2024)
The article focuses on the developments of theological training in die Western Cape Synod of the Dutch Reformed Church (DRC) in the last decade. In this era a Seminary was founded to facilitate ministerial formation for the DRC; Uniting Reformed Church and the Evangelical Lutheran Church of South Africa (ELCSA). The article unpacks the historical, demographic, and especially pedagogical complexities of theological education that aims to build missional leadership capacities. The theology and missional ecclesiology, rhetorical pedagogy and capacity theories are some of the building blocks that the synod utilise to build a new era for theological education.